Do reward and punishment sensitivity change after treatment for anorexia nervosa?. (July 2016) - Harrison, Amy; Sternheim, Lot; O'Hara, Caitlin; Oldershaw, Anna; Schmidt, Ulrike
Abstract: An important question in eating disorders (EDs) is why people continue to pursue the perceived benefits of the illness in spite of devastating physical, psychological and social consequences. In investigating this, previous studies have highlighted a profile of low reward and high punishment sensitivity in anorexia nervosa. Treatments have attempted to target this presentation in therapy although little is known about whether it is possible to do so, thus helping individuals to use more flexible, adaptive and less anxiety-driven responses to their own internal and external environments. In this longitudinal study, 77 outpatients receiving psychological treatment (mean age = 26.6; SD = 7.90) completed the Carver and White (1994) BIS/BAS Scales before and after treatment. There was a small-sized reduction in BIS anxiety (d = 0.33) after, compared to before treatment. There were no main effects of illness duration, nor treatment dosage (number of sessions attended) on reward and punishment sensitivity after, compared to before treatment. Future work could explore whether small reductions in anxiety may predict long-term recovery, given mood difficulties are a key maintaining factor in contemporary models of EDs. Highlights: High punishment and low reward sensitivity are present in anorexia nervosa (AN). Treatments may target this profile although little is known about to what degree. This longitudinal study showed minimal change after outpatient treatment. There was no effect of illness duration or treatment dose. Longer term treatment may be necessary to impact what appear to be key traits of AN.